How to form a team five keys to high performance - Kanaga, Kim; Kossler, Michael E. (Center for Creative Leadership, 2001)
One of the first steps to take toward increasing team effectiveness is to pay attention to how the team is formed. You can head off most of the problems that beset teams during the formation stage by setting a clear direction, building organizational support, creating an empowering team design, identifying key relationships, and monitoring external factors. When a team is formed with the five high-performance principles described in this guidebook, it has a head start on achieving success.
Includes bibliographical references. - Print version record
Keywords: Teams in the workplace; Management -- Employee participation; Équipes de travail; Personnel; Participation à la gestion; BUSINESS & ECONOMICS; Workplace Culture; BUSINESS & ECONOMICS; Corporate Governance; BUSINESS & ECONOMICS; Leadership; BUSINESS & ECONOMICS; Organizational Development; Management; Employee participation